THE IMPORTANCE OF THE MEDICINAL GUAVA PLANT FRUIT IN MEDICINE - Rakhimova Khusnidakhan Abdukarimovna (Scholar Express Journals, 2023)
It is known that about 50% of drugs produced at pharmaceutical enterprises worldwide are made from raw materials of medicinal plants. Cultivation, study of Medicinal Plants of the present day one of the topical issues is. According to the intact Health Organization, 60% of the available medicines are preparations derived from the raw materials of medicinal plants. The long-term consumption of any chemical drug obtained by synthesis in the current ecological environment leads to various complications in living organisms. As noted in the resolution of the Cabinet of Ministers of the Republic on "state protection of medical and drug production sectors of the Republic of Uzbekistan", it is necessary to preserve medicinal plants belonging to the local flora and increase them culturally. Also, one of the urgent problems is the implementation of the domestic introduction of medicinal plants belonging to a foreign flora. The study of the Guava plant and its import into Uzbekistan is considered Mukhim,since the necessary substances contained in this plant have an effective effect in the treatment of cancer, in the cessation of metaztase.
Keywords: Guava; tropical fruit; pulp; ascorbic acid